A recent question on Light dispersion in gravitational theories, led to an implication that confuses me. It appears that the field equation for a massless vector field travelling in a background with non-zero cosmological constant $\Lambda$ becomes: $$(\nabla^b \nabla_b - \Lambda) A^{a} = 0 \tag{1}$$

This looks a lot like the Proca equation. Meaning the cosmological constant can induce an effective mass on the field? And depending on the sign of $\Lambda$, this can look like a tachyon?

Can someone please explain what the error is here, or if not, then help explain what is going on here?

Here are the details in case I'm just making a stupid computational error:

Starting with Einstein's field equations with a cosmological constant $$R_{\mu \nu} - \frac{1}{2} R \, g_{\mu \nu} + \Lambda g_{\mu \nu} = \frac{8 \pi G}{c^4} T_{\mu \nu} \tag{2}$$ we can solve for vacuum $(T_{\mu \nu}=0)$ and find that $$R_{\mu \nu} = \Lambda g_{\mu \nu} \tag{3}$$

The field equations for a massless vector field evolving in a curved space-time are $$ \nabla^b \nabla_b A^{a} - \nabla^a \nabla_b A^b = {R^a}_{b} A^b \tag{4}$$ which if we consider it moving in the cosmological constant background as described by GR, the right hand side becomes $$ {R^a}_{b} A^b = {g^{a}}_b \Lambda A^b = \Lambda A^a \tag{5}$$ In the Lorenz gauge, $\nabla_b A^b = 0$, the field equation can then be simplified to $$(\nabla^b \nabla_b - \Lambda) A^{a} = 0 \tag{6}$$


Actually, the vacuum implies $R_{\mu\nu}=(\frac{R}{2}-\Lambda)g_{\mu\nu}$, so all your uses of $\Lambda$ should have read $\overline{\Lambda}:=\frac{R}{2}-\Lambda$ or some equivalent result. In $n$-dimensional spacetime $g_{\mu\nu}g^{\mu\nu}=n$ so $R=n(\frac{R}{2}-\Lambda)$ and $\overline{\Lambda}=\frac{R}{n}=\frac{2\Lambda}{n-2}$ provided $n\neq 2$.

Your Eq. (6) therefore becomes $(\square -\frac{R}{n})A^a = (\square -\frac{2\Lambda}{n-2})A^a = 0$. You can think of the tachyon question in terms of the sign of $R$ or the sign of $\Lambda$, depending on your preference.

  • $\begingroup$ In 4d space-time with a cosmological constant, GR predicts $R_{\mu\nu} = \Lambda g_{\mu\nu}$ in vacuum. Your math looks find up to $R = n(\frac{R}{2} - \Lambda)$, but that gives $R = \frac{2n}{n - 2}\Lambda$, or simply $R=4\Lambda$ in our usual 4d space-time. Plugging this into the Einstein field equations in vacuum, $R_{ab} -\frac{1}{2}R g_{ab} + \Lambda g_{ab} = 0$, results in $R_{ab}=\Lambda g_{ab}$. $\endgroup$ – PPenguin Sep 17 '17 at 23:24
  • $\begingroup$ @PPenguin So we agree. $\endgroup$ – J.G. Sep 18 '17 at 6:57
  • $\begingroup$ To make it clear, I am only interested in 4d space-time here. So if we do agree, then all you have actually done is point out that $R_{ab} = \Lambda g_{ab}$ means I could replace $\Lambda$ with $R/4$ in the equations. That's true, but I'm not sure how that observation is useful and is more of a comment than an answer. $\endgroup$ – PPenguin Sep 18 '17 at 8:57

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.